A comparative study of lexical bundles in accepted and rejected applied linguistic research article introductions - Eri Kurniawan; Zahra Fadillah Haerunisa (Universitas Syiah Kuala, 2023)
Multi-word expressions referred to as lexical bundles are the important ‘discourse building blocks’ to construct and signal fluent writing, particularly in an attempt to produce high-quality research articles that can be accepted by reputable journals. A number of studies have reported the use of lexical bundles in various sections of research articles, including introductions as the holder of research rationale. In spite of that, attention is barely paid to the comparison between accepted and rejected manuscripts. With the intention to fill this gap, this study is aimed at investigating whether the manifestation of lexical bundles will differ between the introduction sections of accepted and rejected research articles in applied linguistics. A total of 15 introductions for each data group were analyzed under the frameworks of lexical bundles structures (Biber et al., 2004) and functions (Hyland, 2008). Findings reveal that noun phrase-based and research-oriented bundles were respectively detected as the most prevalent main structure and function in both accepted and rejected data sets. Closer inspection, however, evinced a greater frequency and richer variety of lexical bundles in accepted introductions. Even so, this study confirmed that the two datasets exhibit different subcategories of lexical bundles in numerous cases. Implicationally, the findings of this study may shed further light on the comprehension of lexical bundles use in preparing related future studies.